2018
DOI: 10.3390/met8080591
|View full text |Cite
|
Sign up to set email alerts
|

Control and Design of the Steel Continuous Casting Process Based on Advanced Numerical Models

Abstract: The process of continuous casting of steel is a complex technological task, including issues related to heat transfer, the steel solidification process, liquid metal flow and phase transitions in the solid state. This involves considerable difficulty in creating the optimal process control system, which would include the influence of all the physico‐chemical phenomena which may occur. In parallel, there is an intensive development of new mathematical models and an increase in computer performance, therefore co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In the presented numerical model of the primary cooling zone, the boundary conditions may be implemented in three individual ways. The equation below describes the second-type (the Neuman condition) and the third-type of boundary conditions [17,18]: where T a is ambient temperature, K; σ is Stefan–Boltzmann radiation constant, 5.670373 × 10 −8 W m −2 K −4 .…”
Section: Numerical Computingmentioning
confidence: 99%
See 2 more Smart Citations
“…In the presented numerical model of the primary cooling zone, the boundary conditions may be implemented in three individual ways. The equation below describes the second-type (the Neuman condition) and the third-type of boundary conditions [17,18]: where T a is ambient temperature, K; σ is Stefan–Boltzmann radiation constant, 5.670373 × 10 −8 W m −2 K −4 .…”
Section: Numerical Computingmentioning
confidence: 99%
“…The sensitivity analysis has shown that the correctness of numerical calculation results depends on the high accuracy and precision of material-related data implemented in the model [17]. From all the thermophysical parameters, the specific heat along with the latent heat is the most pivotal parameters.…”
Section: Numerical Computingmentioning
confidence: 99%
See 1 more Smart Citation
“…This multiphysical nature in combination with a large scale of industrial casters makes this process challenging for computational modelling. The state of the art of continuous casting numerical simulation is summarized in [2][3][4]. Although much progress is made, accurate defect prediction is still in its beginning.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulation of casting processes has been quite mature at the macroscopic level [9][10][11][12][13], including the finite difference method (FDM), finite element method (FEM) and finite volume method (FVM). Based on these methods, commercial simulation software [14] for the casting process have been developed, such as ProCast, Thercast, MAGMASoft, and Flow3D.…”
Section: Introductionmentioning
confidence: 99%